Portuguese as a Welcoming Language: Breaking Linguistic and Cultural Boundaries - Rocha, Nildiceia Aparecida [UNESP]; da Silveira Gileno, Rosangela Sanches [UNESP] (Springer Nature, 2022)
In the linguistic education process, the reasons for teaching and learning Portuguese for migrants and refugees are associated with the needs related to their insertion in the country. Thus, the circumstances and contexts of the participants must be considered and conducted from the teaching modality of Portuguese for foreigners named Portuguese as a Welcoming Language (PLAc, from the Portuguese “Português como língua de acolhimento”) whose goal is to promote teaching-learning from the perspective of reception and interculturality, aiming at the literacy of sociocultural practices of Brazilian society (GROSSO. Horizontes de Linguística Aplicada, v. 9, n.2, p. 61-77, 2010; São Bernardo, Português como língua de acolhimento: um estudo comimigrantes e pessoas em situação de refúgio no Brasil. Tese (Doutorado em Linguística) Universidade Federal de São Carlos, São Carlos: 2016; Sene, Materialidades e objetivos para o ensino de português como língua deacolhimento: um estudo de caso. Dissertação (Mestrado em Linguística Aplicada) - Universidade de Brasília, Brasília: 2017; LOPEZ and DINIZ, Revista da Sociedade Internacional Português Língua Estrangeira, Brasília, edição especial n. 9, s./p: 2018). From this perspective, it is considered that linguistic and cultural needs are relevant for inclusion in the new social context. Therefore, social, historical, cultural, and psychological issues are part of the planning of activities linked to content, format, and duration (Vieira and Aranha, The ESPecialist 36(1): 2015), since in many cases, the vulnerability of the target audience can generate difficulties for insertion (Amado, Revista da Sociedade Internacional Português Língua Estrangeira - SIPLE, Brasília 7(2): 2013), as well as social maladjustments. Therefore, the text initially traces historically the term and the understanding of the Reception Language, specifically Portuguese as a Welcoming Language (PLAc) or Portuguese Welcoming Language. Then, we present the context in which we carry out the activities and actions of the “Project Portuguese as a Welcoming Language (PLAc) for Venezuelans” offered by a State University in the interior of the State of São Paulo, Brazil, in partnership with the municipality of the city and a religious institution in the same city, from its beginnings to the present day, passing through the face-to-face and online modality. Afterward, we bring the voices of the participants of the referred PLAc project, in which it is possible to observe how the articulation between language and culture has refracted in ruptures of initially perceived barriers and verified discrimination, hence establishing bridges and strengths for the insertion in the new context, in Brazilian culture and in the Portuguese language. Finally, we reflect on the urgency of publicizing and implementing similar projects in Brazilian territory and, why not to say, overseas.
Keywords: Brazilian culture and interculturality; Discrimination; Migrants and refugees; Portuguese as a Welcoming Language